Influence of digital marketing communication and performance effectiveness between b2b companies and clients in Thailand - YONGVONGPHAIBOON, P.; CHANTAMAS, M. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The objectives of this study are to investigate the relative importance of digital marketing communication and CRM in influencing different concepts of trust (social trust and customer trust) and how it leads to firm and customer performance effectiveness in construction steel industries in Thailand. The findings revealed that digital marketing communication and customer relationship management have a positive and significant relation with different aspects of trust through the moderating effect of customer engagement. The results also showed that customer trust has a positive and significant relationship with the firm and customer performance effectiveness. RESUMEN Los objetivos de este estudio son investigar la importancia relativa de la comunicación de marketing digital y CRM para influir en diferentes conceptos de confianza (confianza social y confianza del cliente) y cómo conduce a la eficacia del desempeño de las empresas y los clientes en las industrias del acero para la construcción en Tailandia. En los resultados se encontraron que la comunicación de marketing digital y la gestión de la relación con el cliente tienen un impacto positivo y significativo con diferentes aspectos de la confianza a través del efecto moderador del compromiso del cliente. Los resultados también mostraron que la confianza del cliente tiene una relación positiva y significativa con la eficacia del desempeño de la empresa.